Modified lithium iron phosphate positive electrode material and preparation method thereof

By introducing Zn and vinylphosphonic acid into the lithium iron phosphate positive electrode material, combined with the use of network gelling agents and initiators, a modified lithium iron phosphate positive electrode material was prepared, which solved the performance of the existing positive electrode material at low temperature and magnification. The best problem is that stable discharge performance and efficient lithium ion diffusion are achieved.

CN119503749APending Publication Date: 2025-02-25CHINA NAT PETROLEUM CORP
View PDF 0 Cites 3 Cited by

Patent Information

Application Number
CN202311084840.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-08-25
Publication Date
2025-02-25

AI Technical Summary

Technical Problem

Existing lithium-ion battery positive electrode materials such as LiCoO2, LiMn2O4 and LiFePO4 have problems with unstable structure, fast capacity attenuation, poor low-temperature discharge performance and poor rate discharge performance.

Method used

By adding lithium sources, iron sources, zinc sources and phosphorus sources to water and stir and dissolve, adding network gelling agents and initiators, stirring and reactions, wet gels are obtained, and modified phosphoric acid is prepared by predecomposition, grinding and sintering. Iron lithium positive electrode material.

Benefits of technology

The modified lithium iron phosphate positive electrode material has a stable rate cycle performance, and can maintain excellent discharge performance and stable rate cycle performance at low temperatures. The electron conductivity and the diffusion rate of lithium ions have also been improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119503749A_ABST
    Figure CN119503749A_ABST
Patent Text Reader

Abstract

The invention belongs to the field of chemical energy materials, and discloses a modified lithium iron phosphate positive electrode material and a preparation method thereof.The preparation method comprises the steps that a lithium source, an iron source and a zinc source are added into water to be stirred and dissolved, then a phosphorus source, a network gelling agent and an initiator are added, stirring reaction is conducted, and wet gel is obtained; and pre-decomposing the wet gel, grinding and sintering to obtain the modified lithium iron phosphate positive electrode material. According to the invention, Zn is introduced into the lithium iron phosphate positive electrode material, so that the olivine structure of the positive electrode material and the purity and consistency of the lithium iron phosphate positive electrode material are ensured; and Zn is oxidized into Zn < 2 + > to be doped into a lithium iron phosphate structure, so that vacancies are formed, the lithium ion diffusion rate and conductivity of the lithium iron phosphate positive electrode material are improved, the rate cycle performance of the prepared modified lithium iron phosphate positive electrode material is stable, and excellent discharge performance and stable rate cycle performance can be kept at low temperature.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of chemical energy materials, and in particular relates to a modified lithium iron phosphate positive electrode material and a preparation method thereof. Background Art

[0002] As the energy problem caused by the continuous reduction of oil reserves becomes increasingly severe, there is an urgent need to find a sustainable and environmentally friendly energy. In the development of new energy, the use of natural energy such as wind energy, tidal energy, and solar energy is of great significance, but the process of these energy effects is discontinuous. Large-scale use of these natural energies requires matching energy storage devices. Batteries, especially secondary batteries, are energy storage and conversion devices with high conversion efficiency. They have the advantages of being easy to use, safe, and reliable, and have become one of the effective measures to solve energy problems.

[0003] In recent years, electric vehicles and hybrid vehicles powered by high energy density, long cycle life and environmentally friendly rechargeable lithium-ion batteries have entered thousands of households and gradually changed the way people use energy. When lithium-ion batteries are used as power batteries and energy storage batteries, higher requirements are placed on their energy density and safety. The electrodes of lithium-ion batteries are divided into two parts: positive and negative electrodes. The performance of the positive electrode material determines the electrochemical performance of lithium-ion batteries to a certain extent. At present, the commonly used positive electrode materials for lithium batteries are lithium cobalt oxide (LiCoO2), lithium manganese oxide (LiMn2O4), lithium nickel cobalt manganese oxide (LiCo1-x-yNixMnyO2) and lithium iron phosphate (LiFePO4). The layered LiCoO2 is the earliest commercially produced cathode material. However, due to its unstable structure, the capacity decay is large during high current discharge, and the actual discharge capacity is only 140mAh / g. In addition, the cobalt resources are limited, expensive, and toxic, which limits the application of lithium cobalt oxide lithium-ion batteries. LiMn2O4 has the John-Teller effect, which is prone to structural distortion, resulting in severe capacity decay and poor cycle performance.

[0004] LiCo1-x-yNixMnyO2 has the problems of low structural order and fast capacity decay. The raw materials used in the preparation of LiFePO4 are iron and phosphorus, which are abundant in resources and low in price. LiFePO4 has relatively high theoretical specific capacity of 170mAh / g, excellent thermal stability and chemical stability, long cycle life, and environmental friendliness, making it the most commonly used positive electrode material for lithium-ion power batteries. However, LiFePO4 positive electrode materials have the defects of low conductivity and slow lithium ion diffusion, which leads to poor low-temperature discharge performance and poor rate discharge performance of the battery. Summary of the invention

[0005] In order to overcome the defects of the above-mentioned prior art, the purpose of the present invention is to provide a modified lithium iron phosphate positive electrode material and a preparation method thereof, so as to solve the problems of the above-mentioned prior art.

[0006] To achieve the above object, the present invention provides the following technical solutions:

[0007] A method for preparing a modified lithium iron phosphate positive electrode material, characterized by comprising:

[0008] Adding lithium source, iron source and zinc source into water and stirring to dissolve, then adding phosphorus source, network gelling agent and initiator, stirring to react, and obtaining wet gel;

[0009] The wet gel is pre-decomposed, ground and sintered to obtain a modified lithium iron phosphate positive electrode material.

[0010] Furthermore, the amounts of lithium source, phosphorus source, iron source and zinc source are configured according to the atomic molar ratio of Li, P, Fe and Zn of 1:1:0.8-0.95:0.05-0.2.

[0011] Further, the lithium source includes at least one of lithium carbonate, lithium oxalate and lithium citrate.

[0012] Further, the iron source includes at least one of ferrous sulfate and ferric phosphate.

[0013] Further, the zinc source includes at least one of zinc sulfate, zinc chloride and zinc nitrate.

[0014] Further, the phosphorus source includes vinylphosphonic acid and diammonium hydrogen phosphate.

[0015] Further, the network gelling agent includes any one of acrylamide, N,N-methylenebisacrylamide, dimethylaminoethyl methacrylate and N-isopropylacrylamide.

[0016] Furthermore, the initiator is an inorganic acid ammonium salt, including any one of ammonium persulfate, ammonium nitrate and ammonium carbonate.

[0017] Further, the wet gel is pre-decomposed, ground and sintered, including:

[0018] The pre-decomposition temperature is 170-190°C and the time is 3-4h;

[0019] Grind the pre-decomposed wet gel to a particle size of 0.1 to 0.3 μm;

[0020] The sintering temperature is 700-800°C, the heating rate is 5-8°C / min, and the time is 3-4h.

[0021] On the other hand, the present invention discloses a modified lithium iron phosphate positive electrode material, which is prepared by the method described in the claim above.

[0022] Technical effects and advantages of the present invention:

[0023] 1. The modified lithium iron phosphate positive electrode material prepared by the present invention has stable rate cycle performance and can maintain excellent discharge performance and stable rate cycle performance even at low temperatures.

[0024] 2. The present invention introduces Zn into the lithium iron phosphate positive electrode material. Zn has a strong oxygen-snatching ability at high temperature, which makes the Fe 3+ Reduction to Fe 2+ , and prevent Fe 2+ It is oxidized again, thereby ensuring the olivine structure of the positive electrode material and the purity and consistency of the lithium iron phosphate positive electrode material; and Zn is oxidized to Zn 2+ It is doped into the lithium iron phosphate structure to form vacancies, which improves the lithium ion diffusion rate and conductivity of the lithium iron phosphate positive electrode material. However, the doping amount of Zn needs to be controlled, and excessive doping will produce agglomeration.

[0025] 3. The present invention uses vinylphosphonic acid and diammonium hydrogen phosphate as phosphorus sources, which effectively improves the electronic conductivity and lithium ion diffusion rate of the modified lithium iron phosphate positive electrode material, and can maintain excellent discharge performance and stable rate cycle performance at low temperatures.

[0026] Other features and advantages of the present invention will be described in the following description, and partly become apparent from the description, or understood by practicing the present invention. The purpose and other advantages of the present invention can be realized and obtained by the structures pointed out in the description, claims and drawings. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] Figure 1 This is a flow chart of a method for preparing a modified lithium iron phosphate positive electrode material of the present invention;

[0028] Figure 2 It is a schematic diagram of the modified lithium iron phosphate positive electrode material of the present invention. DETAILED DESCRIPTION

[0029] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0030] like Figure 1 As shown, the present invention provides a method for preparing a modified lithium iron phosphate positive electrode material, comprising:

[0031] Adding lithium source, iron source and zinc source into water and stirring to dissolve, then adding phosphorus source, network gelling agent and initiator, stirring to react, and obtaining wet gel;

[0032] The wet gel is pre-decomposed, ground and sintered to obtain a modified lithium iron phosphate positive electrode material.

[0033] In some embodiments of the present invention, the amounts of lithium source, phosphorus source, iron source and zinc source are configured according to the atomic molar ratio of Li, P, Fe and Zn of 1:1:0.8-0.95:0.05-0.2.

[0034] In some embodiments of the present invention, the lithium source includes at least one of lithium carbonate, lithium oxalate and lithium citrate.

[0035] In some embodiments of the present invention, the iron source includes at least one of ferrous sulfate and ferric phosphate.

[0036] In some embodiments of the present invention, the zinc source includes at least one of zinc sulfate, zinc chloride, and zinc nitrate.

[0037] In some embodiments of the present invention, the phosphorus source includes vinylphosphonic acid and diammonium phosphate.

[0038] It should be noted that the phosphonic acid groups contained in vinyl phosphonic acid rely on the complexation of metal ions by the phosphonic acid groups and the interpenetrating cross-linking between gels formed in subsequent polymerization, thereby obtaining a double network hydrogel modified with phosphonic acid groups and complexed with metal ions. Sintering the double network hydrogel can obtain a positive electrode material with stable electrochemical properties.

[0039] In some embodiments of the present invention, the network gelling agent includes any one of acrylamide, N,N-methylenebisacrylamide, dimethylaminoethyl methacrylate and N-isopropylacrylamide.

[0040] In some embodiments of the present invention, the initiator is an inorganic acid ammonium salt, including any one of ammonium persulfate, ammonium nitrate and ammonium carbonate.

[0041] In some embodiments of the present invention, the wet gel is pre-decomposed, ground, and sintered, comprising:

[0042] The pre-decomposition temperature is 170-190°C and the time is 3-4h;

[0043] Grind the pre-decomposed wet gel to a particle size of 0.1 to 0.3 μm;

[0044] The sintering temperature is 700-800°C, the heating rate is 5-8°C / min, and the time is 3-4h.

[0045] On the other hand, Figure 2As shown, the present invention discloses a modified lithium iron phosphate positive electrode material, which is prepared by the above method.

[0046] In order to better illustrate the present invention, the following examples and comparative examples are provided.

[0047] Example 1

[0048] S1: According to the atomic molar ratio of Li:P:Fe:Zn of 1:1:0.9:0.1, weigh out a lithium source (lithium carbonate), a phosphorus source (vinylphosphonic acid and diammonium hydrogen phosphate in a molar ratio of 1:3), an iron source (ferrous sulfate) and a zinc source (zinc sulfate).

[0049] S2: Add 1 mol lithium source, 0.9 mol iron source and 0.1 mol zinc source into water and stir magnetically for 2 h to dissolve, then add 1 mol phosphorus source, 2 mol network gelling agent (acrylamide) and 0.5 mol initiator (ammonium persulfate), stir to react and obtain a wet gel.

[0050] S3: The wet gel was placed in a resistance furnace at 180°C for 3 h for pre-decomposition, and then ground to a particle size of about 0.2 μm to obtain a precursor powder.

[0051] S4: The precursor powder is placed in a tubular furnace, and in a nitrogen atmosphere, the temperature is increased to 750°C at a heating rate of 6°C / min, and sintered for 4 hours to obtain a modified lithium iron phosphate positive electrode material.

[0052] Example 2

[0053] S1: According to the atomic molar ratio of Li:P:Fe:Zn of 1:1:0.95:0.05, a lithium source (lithium oxalate), a phosphorus source (vinylphosphonic acid and diammonium hydrogen phosphate in a molar ratio of 1:3), an iron source (ferric phosphate) and a zinc source (zinc chloride) were weighed respectively.

[0054] S2: Add 1 mol lithium source, 0.95 mol iron source, and 0.05 mol zinc source into water and stir magnetically for 2 h to dissolve. Then add 1 mol phosphorus source, 2 mol network gelling agent (N,N-methylenebisacrylamide) and 0.5 mol initiator (ammonium nitrate), stir to react, and obtain a wet gel.

[0055] S3: The wet gel was placed in a resistance furnace at 170°C for 4 h for pre-decomposition, and then ground to a particle size of about 0.1 μm to obtain a precursor powder.

[0056] S4: placing the precursor powder in a tubular furnace, heating the temperature to 700°C at a heating rate of 5°C / min under a nitrogen atmosphere, and sintering for 3.5 hours to obtain a modified lithium iron phosphate positive electrode material.

[0057] Example 3

[0058] S1: According to the atomic molar ratio of Li:P:Fe:Zn of 1:1:0.85:0.15, a lithium source (lithium citrate), a phosphorus source (vinylphosphonic acid and diammonium hydrogen phosphate in a molar ratio of 1:3), an iron source (ferrous sulfate) and a zinc source (zinc nitrate) were weighed respectively.

[0059] S2: Add 1 mol lithium source, 0.85 mol iron source and 0.15 mol zinc source into water and stir magnetically for 2 h to dissolve. Then add 1 mol phosphorus source, 2 mol network gelling agent (dimethylaminoethyl methacrylate) and 0.5 mol initiator (ammonium carbonate), stir and react to obtain a wet gel.

[0060] S3: The wet gel was placed in a resistance furnace at 190°C for pre-decomposition for 3.5 hours, and then ground to a particle size of about 0.3 μm to obtain a precursor powder.

[0061] S4: placing the precursor powder in a tubular furnace, heating the temperature to 800°C at a heating rate of 8°C / min under a nitrogen atmosphere, and sintering for 3 hours to obtain a modified lithium iron phosphate positive electrode material.

[0062] Comparative Example 1

[0063] S1: According to the atomic molar ratio of Li:P:Fe:Zn of 1:1:0.9:0.1, weigh out a lithium source (lithium carbonate), a phosphorus source (diammonium hydrogen phosphate), an iron source (ferrous sulfate) and a zinc source (zinc sulfate).

[0064] S2: Add 1 mol lithium source, 0.9 mol iron source and 0.1 mol zinc source into water and stir magnetically for 2 h to dissolve, then add 1 mol phosphorus source, 2 mol network gelling agent (acrylamide) and 0.5 mol initiator (ammonium persulfate), stir to react and obtain a wet gel.

[0065] S3: The wet gel was placed in a resistance furnace at 180°C for 3 h for pre-decomposition, and then ground to a particle size of about 0.2 μm to obtain a precursor powder.

[0066] S4: The precursor powder is placed in a tubular furnace, and in a nitrogen atmosphere, the temperature is increased to 750°C at a heating rate of 6°C / min, and sintered for 4 hours to obtain a modified lithium iron phosphate positive electrode material.

[0067] Comparative Example 2

[0068] S1: According to the atomic molar ratio of Li:P:Fe:Zn of 1:1:0.9:0.1, weigh out a lithium source (lithium carbonate), a phosphorus source (vinylphosphonic acid), an iron source (ferrous sulfate) and a zinc source (zinc sulfate).

[0069] S2: Add 1 mol lithium source, 0.9 mol iron source and 0.1 mol zinc source into water and stir magnetically for 2 h to dissolve, then add 1 mol phosphorus source, 2 mol network gelling agent (acrylamide) and 0.5 mol initiator (ammonium persulfate), stir to react and obtain a wet gel.

[0070] S3: The wet gel was placed in a resistance furnace at 180°C for 3 h for pre-decomposition, and then ground to a particle size of about 0.2 μm to obtain a precursor powder.

[0071] S4: The precursor powder is placed in a tubular furnace, and in a nitrogen atmosphere, the temperature is increased to 750°C at a heating rate of 6°C / min, and sintered for 4 hours to obtain a modified lithium iron phosphate positive electrode material.

[0072] Comparative Example 3

[0073] S1: According to the atomic molar ratio of Li:P:Fe:Zn of 1:1:0.9:0.1, weigh out a lithium source (lithium carbonate), a phosphorus source (vinylphosphonic acid and diammonium hydrogen phosphate in a molar ratio of 1:3), an iron source (ferrous sulfate) and a zinc source (zinc sulfate).

[0074] S2: Add 1 mol lithium source, 0.9 mol iron source and 0.1 mol zinc source into water and stir magnetically for 2 h to dissolve, then add 1 mol phosphorus source, 2 mol network gelling agent (acrylamide) and 0.5 mol initiator (ammonium persulfate), stir to react and obtain a wet gel.

[0075] S3: The wet gel was placed in an oven at 50°C to dry, and then ground to a particle size of about 0.2 μm to obtain a precursor powder.

[0076] S4: The precursor powder is placed in a tubular furnace, and in a nitrogen atmosphere, the temperature is increased to 750°C at a heating rate of 6°C / min, and sintered for 4 hours to obtain a modified lithium iron phosphate positive electrode material.

[0077] Comparative Example 4

[0078] S1: According to the atomic molar ratio of Li:P:Fe of 1:1:1, a lithium source (lithium carbonate), a phosphorus source (vinylphosphonic acid and diammonium hydrogen phosphate in a molar ratio of 1:3), and an iron source (ferrous sulfate) were weighed respectively.

[0079] S2: Add 1 mol of lithium source and 1 mol of iron source into water and stir magnetically for 2 h to dissolve, then add 1 mol of phosphorus source, 2 mol of network gelling agent (acrylamide) and 0.5 mol of initiator (ammonium persulfate), stir to react, and obtain a wet gel.

[0080] S3: The wet gel was placed in an oven at 50°C to dry, and then ground to a particle size of about 0.2 μm to obtain a precursor powder.

[0081] S4: The precursor powder is placed in a tubular furnace, and in a nitrogen atmosphere, the temperature is increased to 750°C at a heating rate of 6°C / min, and sintered for 4 hours to obtain a modified lithium iron phosphate positive electrode material.

[0082] Comparative Example 5

[0083] S1: According to the atomic molar ratio of Li:P:Fe:Zn of 1:1:0.9:0.3, a lithium source (lithium carbonate), a phosphorus source (vinylphosphonic acid and diammonium hydrogen phosphate in a molar ratio of 1:3), an iron source (ferrous sulfate) and a zinc source (zinc sulfate) were weighed respectively.

[0084] S2: Add 1 mol lithium source, 0.9 mol iron source and 0.3 mol zinc source into water and stir magnetically for 2 h to dissolve, then add 1 mol phosphorus source, 2 mol network gelling agent (acrylamide) and 0.5 mol initiator (ammonium persulfate), stir to react, and obtain a wet gel.

[0085] S3: The wet gel was placed in a resistance furnace at 180°C for 3 h for pre-decomposition, and then ground to a particle size of about 0.2 μm to obtain a precursor powder.

[0086] S4: The precursor powder is placed in a tubular furnace, and in a nitrogen atmosphere, the temperature is increased to 750°C at a heating rate of 6°C / min, and sintered for 4 hours to obtain a modified lithium iron phosphate positive electrode material.

[0087] Comparative Example 6

[0088] S1: According to the atomic molar ratio of Li:P:Fe:Zn of 1:1:0.99:0.01, weigh out a lithium source (lithium carbonate), a phosphorus source (vinylphosphonic acid and diammonium hydrogen phosphate in a molar ratio of 1:3), an iron source (ferrous sulfate) and a zinc source (zinc sulfate).

[0089] S2: Add 1 mol lithium source, 0.99 mol iron source and 0.01 mol zinc source into water and stir magnetically for 2 h to dissolve, then add 1 mol phosphorus source, 2 mol network gelling agent (acrylamide) and 0.5 mol initiator (ammonium persulfate), stir to react, and obtain a wet gel.

[0090] S3: The wet gel was placed in a resistance furnace at 180°C for 3 h for pre-decomposition, and then ground to a particle size of about 0.2 μm to obtain a precursor powder.

[0091] S4: The precursor powder is placed in a tubular furnace, and in a nitrogen atmosphere, the temperature is increased to 750°C at a heating rate of 6°C / min, and sintered for 4 hours to obtain a modified lithium iron phosphate positive electrode material.

[0092] The modified lithium iron phosphate positive electrode materials prepared in Examples 1 to 3 and Comparative Examples 1 to 6 were assembled into batteries, and the electrochemical properties were measured.

[0093] The battery preparation method is as follows: using N-methylpyrrolidone as a solvent, adding modified lithium iron phosphate positive electrode material powder, conductive carbon black and polyvinylidene fluoride in a mass ratio of 80:10:10 to N-methylpyrrolidone, mixing evenly and grinding to form a slurry, using a coating machine to evenly coat the slurry on an aluminum foil, placing the aluminum foil in a forced air drying oven at 55°C for 5 hours, and then transferring it to a vacuum drying oven at 110°C for vacuum drying for 15 hours, and after sheeting, using a sheet cutter to cut it into a disc (positive electrode sheet) with a diameter of 18 mm, and assembling it in the order of positive electrode shell, positive electrode sheet, electrolyte, diaphragm, electrolyte, lithium sheet, aluminum sheet, spring sheet, and negative electrode shell, and sealing to obtain a button battery for electrochemical performance measurement.

[0094] The electrochemical performance measurement is specifically as follows: measuring the electronic conductivity of the modified lithium iron phosphate positive electrode material, the diffusion rate of lithium ions, the initial discharge capacity (0.5C rate) at room temperature (25°C), the discharge capacity (0.5C rate) after 100 cycles at room temperature, the initial discharge capacity (0.5C rate) at low temperature (5°C), and the discharge capacity (0.5C rate) after 100 cycles at low temperature. The measurement results are shown in Table 1.

[0095] Table 1

[0096]

[0097]

[0098] It can be seen from Table 1 that the modified lithium iron phosphate positive electrode materials prepared in Examples 1-3 of the present invention have stable rate cycling performance, and can maintain excellent discharge performance and stable rate cycling performance at low temperature (5°C), and the electronic conductivity is 2.15-2.47×10 -3 S / cm, the diffusion rate of lithium ions is 2.78-3.06×10 -9 cm 2 / s.

[0099] Comparative Example 1: Based on the embodiment, diammonium hydrogen phosphate is selected as the phosphorus source, and the electronic conductivity and the diffusion rate of lithium ions of the prepared modified lithium iron phosphate positive electrode material are significantly reduced, and the rate cycling performance is unstable.

[0100] Comparative Example 2: Based on the example, vinylphosphonic acid is selected as the phosphorus source, and the prepared modified lithium iron phosphate positive electrode material has insufficient rate cycle performance at low temperature (5°C).

[0101] Comparative Example 3, based on the embodiment, the wet gel was placed in a 50°C oven to dry without pre-decomposition. The electronic conductivity and the diffusion rate of lithium ions of the prepared modified lithium iron phosphate positive electrode material were significantly reduced, and the rate cycling performance was unstable.

[0102] In Comparative Example 4, no zinc source was added on the basis of the embodiment, and the electronic conductivity and the diffusion rate of lithium ions of the prepared modified lithium iron phosphate positive electrode material were significantly reduced, and the rate cycle performance was not stable enough.

[0103] In Comparative Example 5, excessive zinc source is added on the basis of the embodiment, which will cause agglomeration. The electronic conductivity and the diffusion rate of lithium ions of the prepared modified lithium iron phosphate positive electrode material are significantly reduced, and the rate cycle performance is unstable.

[0104] In Comparative Example 6, a small amount of zinc source is added on the basis of the embodiment, and the electronic conductivity and the diffusion rate of lithium ions of the prepared modified lithium iron phosphate positive electrode material are improved, but the rate cycling performance is not stable enough.

[0105] In summary, the present invention introduces Zn into the lithium iron phosphate positive electrode material. Zn has a strong oxygen-snatching ability at high temperature, which makes the Fe 3+ Reduction to Fe 2+ , and prevent Fe 2+ It is oxidized again, thereby ensuring the olivine structure of the positive electrode material and the purity and consistency of the lithium iron phosphate positive electrode material; and Zn is oxidized to Zn 2+ It is doped into the lithium iron phosphate structure to form vacancies, thereby improving the lithium ion diffusion rate and conductivity of the lithium iron phosphate positive electrode material. However, the doping amount of Zn needs to be controlled. The doping should be appropriate. Excessive doping will produce agglomeration. The modified lithium iron phosphate positive electrode material prepared by the present invention has stable rate cycling performance and can maintain excellent discharge performance and stable rate cycling performance even at low temperatures.

[0106] Finally, it should be noted that the above is only a preferred embodiment of the present invention and is not intended to limit the present invention. Although the present invention has been described in detail with reference to the aforementioned embodiments, it is still possible for those skilled in the art to modify the technical solutions described in the aforementioned embodiments or to make equivalent substitutions for some of the technical features therein. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.

Claims

1. A method for preparing a modified lithium iron phosphate positive electrode material, characterized in that: include: Adding lithium source, iron source and zinc source into water and stirring to dissolve, then adding phosphorus source, network gelling agent and initiator, stirring to react, and obtaining wet gel; The wet gel is pre-decomposed, ground and sintered to obtain a modified lithium iron phosphate positive electrode material.

2. The method for preparing a modified lithium iron phosphate positive electrode material according to claim 1, characterized in that: The amounts of lithium source, phosphorus source, iron source and zinc source are configured according to the atomic molar ratio of Li, P, Fe and Zn of 1:1:0.8-0.95:0.05-0.

2.

3. The method for preparing a modified lithium iron phosphate positive electrode material according to claim 1, characterized in that: The lithium source includes at least one of lithium carbonate, lithium oxalate and lithium citrate.

4. The method for preparing a modified lithium iron phosphate positive electrode material according to claim 1, characterized in that: The iron source includes at least one of ferrous sulfate and ferric phosphate.

5. The method for preparing a modified lithium iron phosphate positive electrode material according to claim 1, characterized in that: The zinc source includes at least one of zinc sulfate, zinc chloride and zinc nitrate.

6. The method for preparing a modified lithium iron phosphate positive electrode material according to claim 1, characterized in that: The phosphorus sources include vinylphosphonic acid and diammonium hydrogen phosphate.

7. The method for preparing a modified lithium iron phosphate positive electrode material according to claim 1, characterized in that: The network gelling agent includes any one of acrylamide, N,N-methylenebisacrylamide, dimethylaminoethyl methacrylate and N-isopropylacrylamide.

8. The method for preparing a modified lithium iron phosphate positive electrode material according to claim 1, characterized in that: The initiator is an inorganic acid ammonium salt, including any one of ammonium persulfate, ammonium nitrate and ammonium carbonate.

9. A method for preparing a modified lithium iron phosphate positive electrode material according to any one of claims 1 to 8, characterized in that: The method of pre-decomposing the wet gel, grinding it and sintering it comprises: The pre-decomposition temperature is 170-190°C and the time is 3-4h; Grind the pre-decomposed wet gel to a particle size of 0.1 to 0.3 μm; The sintering temperature is 700-800°C, the heating rate is 5-8°C / min, and the time is 3-4h.

10. A modified lithium iron phosphate positive electrode material, characterized in that: The positive electrode material is prepared by the method according to any one of claims 1 to 9.

Citation Information

Cited By

  • Modified lithium iron phosphate, preparation method thereof, positive electrode material, battery and application

    CN120511297A

  • Modified lithium iron phosphate, preparation method thereof, positive electrode material, battery and application

    CN120511297B

  • High-performance lithium iron phosphate positive electrode material as well as preparation method and application thereof

    CN120622450A